Level of Knowledge and Risk Factors for Visceral Leishmaniasis in a Mining Area of Minas Gerais State, Brazil - Margonari, Carina; Menezes, Júlia Alves; Mayr de Lima Carvalho, Gustavo; Miranda, Júlia Bahia; Furtado de Sousa, Fabrizio; Rêgo, Felipe Dutra; Campos, Aldenise Martins; Monteiro, Carolina Cunha; Madureira, Ana Paula; Andrade Filho, José Dilermando (Interdisciplinary Perspectives on Infectious Diseases, 2020)
Aiming to optimize and adjust leishmaniasis prevention and control measures for the resident population of Pains, state of Minas Gerais, Brazil, a structured questionnaire containing conceptual questions and questions about household characteristics was used to evaluate knowledge level and exposure risk. A total of 396 individuals were interviewed revealing unscientific and fragmented knowledge about the subject for most of the studied population. The female population was found to have 1.68 times more chance of knowing about the disease than the male population, while highly educated individuals were found to have 2.92 times more chances of knowing about leishmaniasis compared to basic educated individuals. All of the respondents reported the presence of, at least, one risk factor, while ages ≥40 years were considered a protective factor compared to younger ages, indicating that older individuals are more likely to recognize risks and protect themselves against leishmaniasis. These results will contribute to the production of didactic materials for the population with respect to their previous knowledge and will provide a basis for control and prophylactic measures.